Membangun Karakter Islami Sejak Dini melalui Pembiasaan Hafalan Juz Amma di Sekolah Dasar - Putri Yovita Anggraini; Ahmad Kirom (Social Science Academic, 2025)
The practice of memorizing Juz ‘Amma at Sempu Elementary School is an important effort in fostering Islamic character from an early age. This program is implemented progressively from grades I to VI, with support from external mentors who have expertise in religious studies. Mentoring aims not only to ensure correct recitation and tajweed application but also to increase students’ motivation to remain consistent in memorization. In addition, the program emphasizes habituation in interacting with the Qur’an, discipline, and the development of students’ memory skills. Common challenges include laziness, lack of focus, boredom, limited time, and insufficient repetition. By applying appropriate methods and continuous guidance from mentors, students can overcome these obstacles, making the memorization process effective and sustainable. As a result, the practice of memorizing Juz ‘Amma has proven capable of developing discipline, patience, and strong religious character in students from an early age.